FENOMENOLOGI: KARL POPPER (FALSIFIKASI) DAN DEKONSTRUKSI J. DERRIDA DALAM PERSPEKTIF ISLAM - Ridho Akbar; Amril Mansur; Eva Dewi (LPPM STAI Ihyaul Ulum Gresik, 2026)
This paper explores the connection between Karl Popper’s concept of falsification and Jacques Derrida’s notion of deconstruction within the framework of phenomenological philosophy and from an Islamic perspective. Using a literature review approach, the study demonstrates that although Popper and Derrida come from different philosophical backgrounds—science and language respectively—they both reject the idea of absolute truth. Popper’s falsification emphasizes the importance of openness to re-examination in scientific processes, while Derrida’s deconstruction challenges fixed meanings in texts and promotes interpretive plurality. In the context of Islamic religious education, both theories provide a critical foundation for developing learning that is reflective, analytical, and appreciative of diverse meanings and interpretations.